Tanggung Jawab Mahasiswa terhadap Etika Akademik dalam Membangun Budaya Ilmiah yang Berintegritas - Suhaila, Lukluk; Humairo, Annisa; Hasibuan, Ilham Nur; Astuti, Rahayu Fuji (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Academic ethics refer to the moral standards and behavioral codes that must be upheld by all members of the academic community. Despite their critical role in shaping intellectual integrity, violations such as plagiarism and dishonesty remain prevalent among students. These issues are often driven by academic pressure, limited ethical awareness, and weak enforcement of institutional regulations. This study aims to provide a comprehensive understanding of students’ responsibility in upholding academic ethics as a foundation for building a culture of scientific integrity in higher education. Using a qualitative descriptive approach, data were collected through questionnaires and semi-structured interviews with selected university students actively engaged in academic and organizational activities. The data were analyzed thematically to identify key patterns related to ethical awareness, challenges, and practices. The findings reveal that while students generally acknowledge the importance of ethical behavior, there remains a significant gap between ethical understanding and its application. Factors such as insufficient training on academic norms, unclear institutional policies, and the lack of exemplary leadership contribute to ethical lapses. The study emphasizes the importance of clear academic codes of conduct, continuous ethical education, and role-model leadership. Institutions must also implement transparent and fair enforcement systems to foster an environment where ethical values are internalized and practiced. A sustainable academic culture rooted in integrity is essential for advancing knowledge and cultivating morally responsible graduates.